The High-Sensitivity C-Reactive Protein to High-Density Lipoprotein Cholesterol Ratio and the Risk of Contrast-Induced Acute Kidney Injury in Patients Undergoing Percutaneous Coronary Intervention - Linxiao Deng; Hua Chen; Qingbo Xu; Kedong Han; Jin Liu; Shiqun Chen; Jingru Deng; Leigang Tian; Zeliang Li; Xiaozhao Lu; Yong Liu; Yan Liang (Reviews in Cardiovascular Medicine, 2024)
Background: The high-sensitivity C-reactive protein to high-density lipoprotein cholesterol ratio (CHR) is a novel biomarker associated with coronary artery disease (CAD) risk. This study aimed to analyze the relationship between CHR and contrast-induced acute kidney injury (CI-AKI). Methods: This retrospective cross-sectional research included 10,917 individuals who underwent PCI. CI-AKI was diagnosed using the Kidney Disease: Improving Global Outcomes (KIDIGO) standard. Univariate and multivariable logistic regression analyses were conducted to examine the association between CHR and CI-AKI, followed by a receiver operating characteristic (ROC) curve of participants to assess the clinical diagnostic performance of CHR on CI-AKI. Results: A total of 1037 patients (9.50%) developed CI-AKI after PCI. The age of individuals averaged 64.1 ± 11.1 years old, with 2511 females (23.0%). A multivariate logistic regression study revealed that higher CHR levels were linked to higher CI-AKI incidence rates ([Q4 vs. Q1]: odds ratio (OR) = 1.89, 95% confidence interval (CI) [1.42 to 2.54], p < 0.001). A restricted cubic spline analysis revealed a linear association between CHR and CI-AKI. ROC analysis indicated that CHR was an excellent predictor of CI-AKI (area under ROC curve = 0.606, 95% CI [0.588 to 0.624]). Conclusions: A high CHR level is strongly associated with increased CI-AKI incidence, suggesting that CHR may be an independent risk factor for CI-AKI. Clinical Trial registration: NCT05050877. https://clinicaltrials.gov/study/NCT05050877?tab=results.